Bone Tissue Engineering and Regeneration: From Discovery to the Clinic—An Overview - O'Keefe, Regis J. (Mary Ann Liebert, Inc., 2011)
A National Institutes of Health sponsored workshop “Bone Tissue Engineering and Regeneration: From Discovery to the Clinic” gathered thought leaders from medicine, science, and industry to determine the state of art in the field and to define the barriers to translating new technologies to novel therapies to treat bone defects. Tissue engineering holds enormous promise to improve human health through prevention of disease and the restoration of healthy tissue functions. Bone tissue engineering, similar to that for other tissues and organs, requires integration of multiple disciplines such as cell biology, stem cells, developmental and molecular biology, biomechanics, biomaterials science, and immunology and transplantation science. Although each of the research areas has undergone enormous advances in last decade, the translation to clinical care and the development of tissue engineering composites to replace human tissues has been limited. Bone, similar to other tissue and organs, has complex structure and functions and requires exquisite interactions between cells, matrices, biomechanical forces, and gene and protein regulatory factors for sustained function. The process of engineering bone, thus, requires a comprehensive approach with broad expertise. Although in vitro and preclinical animal studies have been pursued with a large and diverse collection of scaffolds, cells, and biomolecules, the field of bone tissue engineering remains fragmented up to the point that a clear translational roadmap has yet to emerge. Translation is particularly important for unmet clinical needs such as large segmental defects and medically compromised conditions such as tumor removal and infection sites. Collectively, manuscripts in this volume provide luminary examples toward identification of barriers and strategies for translation of fundamental discoveries into clinical therapeutics.